2010
DOI: 10.1242/dev.054304
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and aging control the quiescence period that follows pancreatic beta cell replication

Abstract: SUMMARYPancreatic beta cell proliferation has emerged as the principal mechanism for homeostatic maintenance of beta cell mass during adult life. This underscores the importance of understanding the mechanisms of beta cell replication and suggests novel approaches for regenerative therapy to treat diabetes. Here we use an in vivo pulse-chase labeling assay to investigate the replication dynamics of adult mouse beta cells. We find that replicated beta cells are able to re-enter the cell division cycle shortly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 30 publications
6
55
3
Order By: Relevance
“…Consistent with the notion that glycolytic flux regulates Ccnd2 expression via the stimulus-secretion-coupling pathway (Salpeter et al, 2010; Salpeter et al, 2011), increasing calcium influx by treating islets with the L-type dependent calcium channel opener, Bay K8644, similarly restored Ccnd2 expression in Nkx6.1 Δadultβ islets (Figure 4H). Significantly, Bay K8644 administration to mice increased the number of insulin + cells expressing Ki67 to control values (Figure 4I), providing in vivo evidence that beta cell proliferation can be rescued by stimulating calcium influx.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with the notion that glycolytic flux regulates Ccnd2 expression via the stimulus-secretion-coupling pathway (Salpeter et al, 2010; Salpeter et al, 2011), increasing calcium influx by treating islets with the L-type dependent calcium channel opener, Bay K8644, similarly restored Ccnd2 expression in Nkx6.1 Δadultβ islets (Figure 4H). Significantly, Bay K8644 administration to mice increased the number of insulin + cells expressing Ki67 to control values (Figure 4I), providing in vivo evidence that beta cell proliferation can be rescued by stimulating calcium influx.…”
Section: Resultssupporting
confidence: 83%
“…Specifically, glucose metabolism is thought to control beta cell proliferation by regulating expression of Cyclin D2 ( Ccnd2 ) (Salpeter et al, 2010; Salpeter et al, 2011), which is a critical regulator of beta cell mass in mice (Georgia and Bhushan, 2004; Kushner et al, 2005). Since Nkx6.1-deficient beta cells have defects in energy production, we examined whether Nkx6.1 deletion affects Ccnd2 mRNA levels.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, most studies on rodent β-cell proliferation are performed in young animals, when β-cells are the most responsive to the induction of proliferation. Several studies (24,6370) have shown that rodent β-cell proliferation capacity declines with age. Surprisingly, we observe that the cell cycle entry induced by cdk6 and cyclin D3 was maintained with age in rat β-cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Because the present monogenic diabetes models maintain a wide range of blood sugar levels for long periods, it will be possible to use these to study the effect of persistent high glucose levels on pancreatic islet cell function and proliferation independent of increased glucose metabolism of these cells (50,51). The Gck ENU models thus enable testing from gene to phenotype to drug.…”
Section: K140e/p417rmentioning
confidence: 99%